Crowdfunding Meets Islamic Social Finance: Integrating Zakah, Waqf, Sadaqah, and FinTech for Sustainable Community Development - Yusuf Isa Sawaba; Adamu Abubakar Muhammad; Ibrahim Abubakar Muhammad; Ismail Iliyasu Danladi; Abdullah A. Afifi; Maryam Babani Muhammad (IDRIS Darulfunun Institute, 2025)
This paper explores the use of FinTech-enabled crowdfunding platforms to integrate Islamic social finance instruments with other similar instruments to enhance sustainable community development. It introduces the Integrated Islamic Crowdfunding and Social Finance Framework (IICSF) to integrate zakah, waqf, sadaqah, and digital crowdfunding to strengthen financial inclusion, institutional transparency, community involvement and sustainable socio-economic development. This study adopts a qualitative research methodology based on document analysis of classical Islamic legal sources and modern literature in Islamic social finance, FinTech, digital philanthropy and sustainable development. The study adopts a conceptual and analytical approach that combines classic Islamic philanthropic principles with cutting-edge digital financial technologies and integrates fragmented streams of scholarship on these areas into an integrative framework. The study found that integrating Islamic social finance with digital crowdfunding may strengthen resource mobilisation, enhance financial transparency, improve efficiency and accountability, encourage donor participation, distribute charitable funds equitably. FinTech such as mobile payment systems, artificial intelligence, block-chain, smart contracts, and digital identification management can build accountability and minimize operational expenses and fraud, as well as restoring public confidence. IICSF creates a collaborative setting amongst financial and civic organisations, including Islamic finance institutions, waqf boards, zakah agencies, crowdfunding portals, regulators, FinTech companies, social entrepreneurs, and the local community. It can also facilitate the financing of poverty eradication, affordable housing and education programmes, access to healthcare, climate action, youth entrepreneurship, and social ventures, among others, and has the potential to contribute significantly to a more inclusive and sustainable community development. This study introduces for the first time the Integrated Islamic Crowdfunding and Social Finance Framework (IICSF) as a comprehensive conceptual model for the integration of Islamic social finance instruments of zakah, waqf, and sadaqah, with FinTech-enabled crowdfunding. The framework addresses how Islamic philanthropic organisations could utilize digital financial technologies to foster greater financial inclusion, improved institutional accountability and performance, community participation and accelerated development. The integrative framework provides a model for a modern Islamic social finance approach capable of meeting social needs of contemporary global societies.